2017
DOI: 10.26710/jbsee.v3i1.182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Employee Motivation on Employee Performance

Abstract: Purpose: The study empirically analyzes the moderating role of government support policy on the relationship between entrepreneurial orientation, technology orientation and performance of small and medium enterprises (SMEs) in northeast Nigeria.   Design/Methodology/Approach: The paper adopts quantitative survey method using structured questionnaires, data was collected from 240 SME owner-managers in northeast Nigeria. The data collected was analyzed using Partial Least Squares PLS-SEM.  Findings: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 4 publications
3
11
0
1
Order By: Relevance
“…This is because during the Covid-19 pandemic, support between co-workers is very important when employees do work form home and there are employees who are forced to come to the office, so the closest co-workers will provide support so that the employee feels safe and calm while at the office. This study is in line with Rahman et al (2019) and Sandhu et al (2016), but not in line with Luhur's research (2015). performance.…”
Section: Discussion Of Research Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This is because during the Covid-19 pandemic, support between co-workers is very important when employees do work form home and there are employees who are forced to come to the office, so the closest co-workers will provide support so that the employee feels safe and calm while at the office. This study is in line with Rahman et al (2019) and Sandhu et al (2016), but not in line with Luhur's research (2015). performance.…”
Section: Discussion Of Research Resultssupporting
confidence: 69%
“…. Research results Rahman et al (2019) and Sandhu et al (2016) stated that motivation has a positive effect on performance. Motivation and job satisfaction factors come from intrinsic and extrinsic factors, the existence of intrinsic and extrinsic factors makes the achievement of performance targets effective.…”
Section: Hypothesis Formulationmentioning
confidence: 93%
See 1 more Smart Citation
“…Various studies have shown a positive correlation between motivation and performance (Khan, 2012;Sandhu et al, 2017;Subari & Riady, 2015;Wright, 2007). In other words, the motivation variable determines the good and bad performance of an employee (Cherian & Jacob, 2013;Tammubua et al, 2015).…”
mentioning
confidence: 99%
“…(2015);Ghaffari & Nazri (2017);Sandhu et al (2017);Kuswati (2020); Ghaffari et al (2020)yang menunjukan bahwa motivasi menjadi pemicu kinerja perusahaan yang semakin meningkat. Artinya kinerja perusahaan akan semakin meningkat karena adanya motivasi dari dalam perusahaan.…”
unclassified